Rapid Heat Acclimation Strategies for Use in the Military - Ashworth, Edward Tom (Auckland University of Technology, 2021)
Military units often deploy abroad to provide international aid for peacekeeping, disaster relief and conflict resolution. Therefore, military personnel are required to operate in environments different to that in which they typically train. Recent, current, and anticipated future deployments involved countries primarily with hot climates, environments that impair physical and cognitive performance. Furthermore, within the military paradigm burdensome loads and protective clothing, as well as the possibility of very short notice deployment can exacerbate the impact on performance as well as safety. Therefore, to ensure both operational success as well as the safety of military personnel it is imperative to have strategies that mitigate the effects of heat. In the initial phase of this thesis a literature review highlighted the problems of operating in the heat within a military context and explored methods that could feasibly improve performance in hot environments. Primarily, the literature review highlighted that due to a multitude of uncontrollable factors within military operations, it was more useful to obtain beneficial heat adaptations through heat acclimation prior to deployment. It also noted that different forms of heat (humid and arid) could cause very different responses, largely due to a limited capacity for sweat to evaporate in humid environments. Operational problems were addressed experimentally by comparing the performance of appropriately dressed military personnel in extreme humid and arid environments. Humid environments elicited a greater thermal strain, likely due to a requirement to carry a heavier load, and reduced sweat evaporation, causing increases in rectal temperature and heart rate, while the arid environment induced a higher skin temperature. Therefore, the first heat acclimation study evaluated the performance of practical, passive, post-exercise heating methods (sauna and hot-water immersion) in a humid environment. Both sauna and hot water immersion reduced rectal temperature, skin temperature, and heart rate, and increased fluid consumption and sweat rate. However, no differences were observed in cognitive performance. Following passive, post exercise heat acclimation, it was examined whether thermal tolerance could be maintained using intermittent heat exposure (IHE); additional passive, post-exercise heating every 2-3 d for ~3 wk. IHE further reduced rectal temperature and increased sweat rate but did not affect performance compared to a control condition that underwent decay, thereby indicating that IHE may not only maintain, but enhance thermal tolerance. Cognitive performance was then further evaluated using a mechanistic study designed to independently elevate rectal temperature to 38.5°C, to determine the influence of core temperature on cognition during exercise in the heat. Elevated rectal temperature did not impair cognitive performance but appeared to increase cerebral oxidative metabolism (assessed using near-infrared spectroscopy). The results indicated that passive, post-exercise IHE, following an initial heat acclimation programme, is a feasible and efficient method to mitigate negative effects of heat on physical performance and to improve safety in military units. While the benefits do not extend to cognitive performance this is likely due to cerebral adjustments that overcome the disturbance to homeostasis caused by the heat.
Keywords: Physiology; Heat; Military; Performance; Health; Acclimation